Survey of official development assistance to Guyana 1996-1997 (UNDP GeorgetownGY, 1998)
Covers the programmes and projects of virtually all the official donors which are active in Guyana. Focuses on development assistance programmes that are current and on-going, and presents descriptions of programmes and projects underway as of the last quarter of 1997, as well as pipeline projects and programmes. Profiles official development assistance to Guyana by themes and sectors, and includes summary tables which seek to provide information on the quantum, sectors of concentration, and sources of development assistance inflows over the reporting period.
DC